The Karolinska Hospital Information System - Mellner, Ch.; Selajstder, H.; Wolodakski, J. (Methods of Information in Medicine, 1974)
The paper gives a report on the Karolinska Hospital Information System in three parts.In part I, the information problems in health care delivery are discussed and the approach to systems design at the Karolinska Hospital is reported, contrasted, with the traditional approach.In part II, the data base and the data processing system, named T1—J 5, are described.In part III, the applications of the data base and the data processing system are illustrated by a broad description of the contents and rise of the patient data base at the Karolinska Hospital.
Keywords: Integrated Medical Information System; Systems Design; Data Base Structure; Systems Adaptability; Problem-oriented Medical Record